OBJEKTIFIKASI PEREMPUAN DALAM NOVEL TELEMBUK: DANGDUT DAN KISAH CINTA YANG KEPARAT KARYA KEDUNG DARMA ROMANSHA (KAJIAN SEMIOTIKA ROLAND BARTHES) - Dewi, Febi Komala (Universitas Jabal Ghafur, 2024)
Thisstudyexaminestheobjectificationofwomenin thenovel Telembuk:Dangdut dan Kisah Cinta yang Keparat. The novel contains the issue of objectification of women, especially sexual objectification which can be studied through the Objectification Theory of Fredrickson Robert and supported by the theory of radical feminism. The main findings of this study are that the character Safitri experiences various forms of objectification, namely: (1) Observational objectification; (2) Tactile objectification; (3) Sexual harassment; (4) Sexual Violence; (5) Exploitation. As a result of the objectification that women receive, women do not have rights over their own bodies, women's bodies are subdued, controlled, and obeyed to serve as an opportunity in the economic industry. The description of theobjectification ofwomen in this novel, accompanied by thelack ofresistancebywomen, canemphasizethatpatriarchalideologyisverydominant and dominates social life, so that women have no voice and remain in a subordinate position.Keywords: Objectification, Exploitation, Women, Telembuk: Dangdut dan Kisah Cinta yang Keparat, Patriarchy.